2006
DOI: 10.1021/jf053128e
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Methanol on the Dynamics of the Retention and Release of Cyprodinil by an Agricultural Soil

Abstract: The influence of methanol on the adsorption of the fungicide cyprodinil by a crop soil was studied by equilibrium measurements and by determining the retention-release dynamics in a continuous stirred flow tank reactor (CSTR). Equilibrium measurements showed the effective coefficient of partition of cyprodinil between soil and solution, K(dc), decreases linearly as the concentration of methanol in the solution increases until a percentage of 20% is reached. In CSTR experiments, the retention of cyprodinil was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The extraction time, defined as an interval from the injection of the mixture of extraction and dispersive solvents to the start of centrifugation in the DLLME procedure, was evaluated in a series of extraction times (5,7,9,11,13, and 25 min). The results show that the extraction equilibrium could be attained within 9 min and the long extraction time had no significant effect on EE ( Fig.…”
Section: Effect Of Extraction Timementioning
confidence: 99%
See 1 more Smart Citation
“…The extraction time, defined as an interval from the injection of the mixture of extraction and dispersive solvents to the start of centrifugation in the DLLME procedure, was evaluated in a series of extraction times (5,7,9,11,13, and 25 min). The results show that the extraction equilibrium could be attained within 9 min and the long extraction time had no significant effect on EE ( Fig.…”
Section: Effect Of Extraction Timementioning
confidence: 99%
“…Especially for cyprodinil, difenoconazole, myclobutanil, and spiroxamine (Fig. ), the mechanism of action is based on the inhibition of methionine biosynthesis, the transport processes in the plasmatic membrane, fungal lanosterol‐14α‐demethylase activity, are four fungicides, which have a different mode of action compared to traditional fungicides . The occurrences of these fungicides in sediment related to crop production are very useful to evaluate the potential risks of freshwater fish and aquatic organisms under cropland use .…”
Section: Introductionmentioning
confidence: 99%
“…Also, presence of organic co-solvents in the soil solution influences the partition and kinetics in laboratory [8]. However, influence of solid adjuvants on the soil-water partition experiments of metalaxyl is not published yet.…”
Section: Introductionmentioning
confidence: 99%
“…A linear adsorption model involving non-equilibrium conditions and an irreversible adsorption term reproduces prior results concerning the impact of transport. In a study carried out in an agricultural field near Ourense, Spain, the influence of methanol on the dynamics of Cyprodinil retention and release was studied through an analysis of agricultural soil (López-Periago et al, 2006). The results of the influence of methanol on the adsorption of Cyprodinil concluded that the effective partition coefficient of Cyprodinil between the soil and the solution, Kdc, decreases linearly as the concentration of methanol in the solution increases until a percentage of 20 % is reached.…”
Section: Cyprodinilmentioning
confidence: 99%